2019
DOI: 10.1038/s41467-019-09798-3
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping ciliary dynamics and coordination in response to CFTR-modulators in Cystic Fibrosis respiratory epithelial cells

Abstract: Personalized approaches for systematically assessing ciliary beat dynamics and for drug testing would improve the challenging task of diagnosing and treating respiratory disorders. In this pilot study, we show how multiscale differential dynamic microscopy (multi-DDM) can be used to characterize collective ciliary beating in a non-biased automated manner. We use multi-DDM to assess the efficacy of different CFTR-modulating drugs in human airway epithelial cells derived from subjects with cystic fibrosis (ΔF508… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…In these systems also the kinematic properties of the fluid (viscosity, and, if the fluid is viscoelastic, it's full rheological behaviour) are crucial. We saw clear evidence of this in experiments where the cilia frequency but also the range of coordination changed dramatically with mucus washing and drug treatment, in CF cells [43].…”
Section: Focus On What Physical Aspects Allow Cilia To Beat Cooperatimentioning
confidence: 74%
See 1 more Smart Citation
“…In these systems also the kinematic properties of the fluid (viscosity, and, if the fluid is viscoelastic, it's full rheological behaviour) are crucial. We saw clear evidence of this in experiments where the cilia frequency but also the range of coordination changed dramatically with mucus washing and drug treatment, in CF cells [43].…”
Section: Focus On What Physical Aspects Allow Cilia To Beat Cooperatimentioning
confidence: 74%
“…Our team has recently demonstrated a new video analysis technique we called multi-DDM to extract information from high frame-rate videos of cells in ALI culture [42] [43]. The basic property of cilia beating is their frequency (CBF) but a wealth of other information is present in videos of cells at ALI, and connected to the fundamental concepts and open questions introduced earlier.…”
Section: Experimental Approachesmentioning
confidence: 99%
“…Ex vivo studies have revealed direct effects of CFTR modulators on the function of neutrophils [ 69 , 109 , 124 , 125 ], macrophages [ 126 , 127 , 130 ], lymphocytes [ 131 , 132 , 133 ], epithelial cells [ 134 , 135 ], and their signalling pathways [ 124 , 128 , 132 ]. There have been additional effects of CFTR modulators demonstrating improvements in MCC including LCI, mucus plugging, and air trapping [ 117 , 121 , 122 ], as well as effects on ciliary function [ 143 ]. However, despite these findings, uncertainty remains as to whether these effects are directly attributable to modulator effects on target cells or whether they are secondary to modification of the diseased airway environment.…”
Section: Discussionmentioning
confidence: 99%
“…Timing is likely to be a key determinant of modulator effects on inflammation, as those with established bronchiectasis and embedded airway infection are likely to continue to exhibit airway inflammation. Furthermore, although CFTR modulators may improve the regenerative properties of epithelial cells and macrophages [ 143 , 144 ], there is no evidence that they can reverse existing disease or the progression of lung function decline; therefore, CFTR modulators may be most effectively utilised as a preventative strategy. This is supported by studies in the G551D-mutated CF ferret model, in which the initiation of IVA treatment in utero resulted in improved pancreatic function and growth and prevented mucus accumulation and bacterial infection in the lungs [ 145 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation